Criteria for affordable housing performance measurement: A review - Esruq-Labin, A.M.J.; Che-Ani, Adi Irfan; Tawil, N.M.; Mohd Nawi, Mohd Nasrun; Othuman Mydin, M.A. (EDP Sciences, 2014)
A home is one of the basic human needs, thus a new concept known as Grow Home has risen. This concept was established to encourage more families to buy their own houses.The Grow Home concept is based on the notion of affordable housing.This paper aims to explore a proposal for affordable housing measurement with six assessment components.In other words, this work intends to study factors that can affect affordable housing assessment.In this paper, we investigated the 20 criteria for affordable housing assessment given by Mulliner and Maliene in their study. Then, we rearranged these criteria into five components, and added the Grow Home component. Each component has different criteria.Finally, six affordable housing measurement components are identified, namely, income ratios, loans and accommodations, facilities and services, safety and comfort, quality management, and Grow Home.These components are also considered as main factors that directly affect affordable housing.This study aspires to contribute to existing literature by proposing six assessment components as a measurement of affordable housing.